2012
DOI: 10.1042/cs20110374
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor activation reduces ischaemic brain damage following stroke in Type 2 diabetic rats

Abstract: Diabetes is a strong risk factor for premature and severe stroke. The GLP-1R (glucagon-like peptide-1 receptor) agonist Ex-4 (exendin-4) is a drug for the treatment of T2D (Type 2 diabetes) that may also have neuroprotective effects. The aim of the present study was to determine the efficacy of Ex-4 against stroke in diabetes by using a diabetic animal model, a drug administration paradigm and a dose that mimics a diabetic patient on Ex-4 therapy. Furthermore, we investigated inflammation and neurogenesis as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
116
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 57 publications
3
116
3
3
Order By: Relevance
“…Post‐stroke treatment with peripherally‐administered exendin‐4 in diabetic rodents resulted in a reduction of infarct volume in a dose‐dependent manner117. Combined pre‐ and post‐treatment with peripherally‐administered linagliptin in diabetic rodents showed a trend toward a decrease in infarct volume118.…”
Section: Type 2 Diabetes Mellitus Stroke and Incretin‐based Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Post‐stroke treatment with peripherally‐administered exendin‐4 in diabetic rodents resulted in a reduction of infarct volume in a dose‐dependent manner117. Combined pre‐ and post‐treatment with peripherally‐administered linagliptin in diabetic rodents showed a trend toward a decrease in infarct volume118.…”
Section: Type 2 Diabetes Mellitus Stroke and Incretin‐based Therapiesmentioning
confidence: 99%
“…After stroke, microglial activation, an inflammatory response, induces various neurotoxic free radicals, cytotoxic and pro‐inflammatory mediators, and contributes to infarct progression114, 116. Rodent models showed inhibited microglial activation and microglial migration, thereby suppressing the inflammatory response induced by ischemic stroke116, 117. In addition, rodent models of ischemic stroke showed that incretin‐based therapies might protect against oxidative stress and neuronal cell death114, 115, 117.…”
Section: Type 2 Diabetes Mellitus Stroke and Incretin‐based Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Существует ряд работ, в которых продемонстриро-вано защитное действие ГПП-1 в условиях транзиторной фокальной ишемии головного мозга у животных [21][22][23][24][25][26].…”
Section: нейропротективное действие инкретиномиметиковunclassified
“…Не менее показательно исследование, проведенное в 2012 г. V. Darsalia [26]. Крысам линии Goto-Kakizaki в течение 4 недель внутрибрюшинно вводился эксен-дин-4 в дозах 0,1, 1 и 5 мкг/кг 2 раза в день, что сопо-ставимо с дозами, используемыми для лечения СД2 у человека, в пересчете на массу тела.…”
Section: нейропротективное действие инкретиномиметиковunclassified